Editorial: Antimicrobials in Wildlife and the Environment - de la Torre, Ana; Hartmann, Alain; Wester, Astrid Louise; Aminov, Rustam (Frontiers in Microbiology, 2021)
Antimicrobial resistance (AMR) is a major threat to both human and animal health since it significantly diminishes the therapeutic options available. Significant amounts of the antimicrobials used in humans and animals are excreted into the environment essentially unchanged, or as metabolites that still retain antimicrobial activity. They reach the environment via direct excretion by pasture animals, from discharges from wastewater treatment plants, via application of manure and sludge to agricultural fields, or direct application of antimicrobials in aquaculture. The release of antimicrobials into the environment can exert a selective pressure on environmental microbiota, leading to the selection of antimicrobial resistance genes (ARGs) in a variety of ecosystems. Thus, the microbiota of plants, wild animals and the environmental microbiota in general can be affected. Another way of dissemination of ARGs into the environmental ecosystems is via AMR bacteria in animal and human faeces. The resulting pool of ARGs in the environment can be considered as self-replicating genetic pollutants, with the possibilities of horizontal transfer, recombination, and generation of a broader diversity of ARGs. From this pool, ARGs can be reintroduced back to human and animal pathogens, thus contributing to the global problem of AMR.